Web-based volunteer management system - Chang, Wei Hang (2025)
This project focuses on developing a robust web-based Volunteer Management System (VMS) to enhance organisational efficiency in volunteer coordination. The system addresses common pain points in traditional volunteer management, including inefficient skill matching, poor geographical allocation, and low engagement retention. Through comprehensive analysis of existing VMS platforms, critical limitations were identified in dynamic skill assessment and location-aware scheduling. The proposed solution utilises React.js for frontend development, supported by a Node.js backend and MySQL database, creating a responsive and scalable platform. Key innovations include a weighted skill-matching algorithm that evaluates both skills importance level required and volunteer proficiencies, a distance-based matching algorithm using Google Maps Distance Matrix API, and leaderboard gamification elements for volunteer contribution recognition. Since the universe of possible volunteer skills is too broad, focusing on a single domain helps reduce the scope of skills to a manageable and realistic level. For demonstration purposes, this project applies the system to the animal welfare domain. However, the skill framework is designed to be domain-tailorable, allowing the same system to be adapted for other sectors such as education, healthcare, or disaster relief. The system offers comprehensive functionalities such as event creation, event modification, event application, and volunteer leaderboard. By integrating these features, the VMS provides organisations with a unified platform for volunteer onboarding, event coordination, and long-term engagement, while offering volunteers a more personalised and accessible experience.